Estimation of Genetic Parameters and Trait Association in Wheat (Triticum aestivum L.) Genotypes - Chapagain, Sujan; Kandel, Bishnu Prasad; Adhikari, Apekshya; Poudel, Ankur; Kandel, Manoj (Journal of the Institute of Agriculture and Animal Science, 2025)
Genetic diversity is important for effective selection and genetic improvement in breeding programs. A study was conducted at Rampur, Chitwan, to study genetic parameters and the association between yield and yield-attributing traits. Thirty-six wheat genotypes were evaluated in an alpha lattice design with two replications. Effective tillers showed the highest genotypic coefficient of variation (GCV) (25.87%) and phenotypic coefficient of variation (27.61%). The difference between PCV and GCV was minimal for the studied traits. Grain yield recorded the highest broad-sense heritability (95%). Grain yield was positively correlated with harvest index, flag leaf area, plant height, and biological yield at both the genotypic and phenotypic levels (p < 0.05). Future breeding programs should prioritize these traits to improve wheat yield potential.